The Paris Agreement on Climate Change: Efficiency of Mitigation Obligation - Al Mamun, Md Jahid (Dhaka University Law Journal, 2022)
The ‘Paris Climate Treaty’ is the first MEA (Multilateral Environmental Agreement) which imposes mitigation obligations not only on developed countries but also on developing country Parties. The Agreement actually extended the mitigation obligations enshrined under the UNFCCC and the Kyoto Protocol. It has created a universal binding obligation to take domestic actions to achieve the target of reducing emissions of GHG set out by the domestic (“bottom-up”) process. PA has recognized the best available science to carry on mitigation actions. It requires the Parties to undertake a continuous planning process to mitigate climate change impacts set out in NDC every five years. This Agreement requires a more ambitious NDC containing progression of mitigation commitment from the previous NDC. Though a ‘mandatory enforcement mechanism’ or ‘penalty for non-compliance with mitigation obligations is absent in the Agreement, the mandatory procedural obligation makes us optimistic that the target will be achieved. The information relating to mitigation actions is subject to technical expert review. For assessing the overall and collective progress towards achieving the PA’s long-term mitigation goals, the Agreement requires a “global stocktake” in 2023 and after that time in every five years. There is a “transparent, non-adversarial and non-punitive” expert-based measure to facilitate compliance with provisions containing mitigation obligations. Many Parties are committed to shifting to renewable energy and imposing a carbon tax in their NDCs to achieve their desired mitigation pledges. Many countries have started to invest in cheaper zero-carbon goods and services. When such cheaper zero-carbon goods and services capture the market, then the mitigation target will be fulfilled easily. PA is a universal consensual document. Though it is confronted with many challenges, its strong foundation and efficient mitigation obligation make us optimistic that the overall mitigation targets will be achieved and that mother earth will be safe from being “hell”. This paper shall discuss the mitigation goal and nature of the mitigation obligation under the PA and finally analyze the efficiency of the mitigation strategy. Dhaka University Law Journal, 2022, 33(1), 99-120